Patient Involvement in Diabetes Care: Greek Study of Decision Aids Inconclusive - Bittner, Dennis (MD Conference Express, 2014)
he high cost of treatment and large variation in the quality of patient care are major concerns in the treatment of type 2 diabetes mellitus. Increasing the degree of patient involvement in decisions related to treatment of their condition has been advocated in current T2DM guidelines and has been shown to improve the overall quality of care. This article presents preliminary results from the multicenter, cluster-randomized Diabetes Medication Choice Cards Trial in Greece [NCT01861756; EASD 2014 (poster 1077)] evaluating use of the Diabetes Medication Choice Decision Aids.